The Effect of Chicken Manure and Triple Super Phospat Fertilizer on The Growth of Purple Cabbage (Brassica oleracea var. Capitata) on Andisol - Made Suarta; I Gusti Made Arjana; I Wayan Drana Nugraha (Warmadewa University Press, 2023)
Cabbage plants (Brassica oleracea) belong to the Brassicaceae family, is a vegetable that is widely cultivated by farmers in rural Indonesia. In an effort to increase the productivity of purple cabbage it is necessary to carry out soil management. Andisol is one type of soil that is relatively fertile but has a high level of P absorption so it is necessary to add Chicken Manure and TSP Fertilizer. The purpose of this study is to determine the effect of treatment and response from the combination of treatment on the application of chicken manure and TSP fertilizer on the growth and production of purple cabbage plants. The research design used was a group randomized design (RAK) with 2 factors arranged factorially. The first factor is chicken manure fertilizer which consists of 3 levels, namely: K1 = chicken manure fertilizer 10 tons / ha (50 grams / polybag), K2 = chicken manure fertilizer 20 tons / ha ( 100 grams / polybag) and, K3 = chicken manure fertilizer 30 tons / ha ( 150 grams / polybag). The second factor of TSP fertilizer consists of 3 levels, namely: T1 = TSP 200 kg / ha ( 1 gram / polybag), T2 = TSP 300 kg / ha ( 1.5 grams / polybag) and, T3 = TSP 400 kg / ha ( 2 grams / polybag). Treatment of Chicken Manure (K), TSP fertilizer, and Interaction (KxT) had no real effect (P â‰¥0.05) on the variables of maximum plant height, maxmium leaf count, root length, flower crop diameter and wet weight of crop per plant.